Components and validity of risk scores for screening for Type 2 diabetes mellitus - Nguyen, Chung; Lee, Andy; Binns, Colin (Future Medicine Ltd, 2012)
Diabetes is the fastest growing chronic disease worldwide. Conventional diagnostic tests, such as fasting plasma glucose, oral glucose tolerance test and glycosylated hemoglobin, are invasive and relatively expensive for application in low-income developing countries. Diabetes Risk Score has emerged as a practical screening tool during the past decade. The purpose of this review is to evaluate the components and validity of risk scores for the screening and early detection of Type 2 diabetes mellitus.